(3OQhS hJeGQjf eMdhdI s - (3UGdM(B, (3HRIs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2020)
(3jJVef gGPG GdcJGH ebGQHI acQjI Mhd GdLHGjI ef NdGd GdJWQb deaghegG heHGOFgG , CgOGagG, GdVQjHI aj GdacQ GdGbJUGOj, hGdCSS GdbGfhfjI ddVQjHI hcPG GdGdJRGeGJ GdLHGFjI , JMOjO GdQHM GdLHGFj, GdVQjHI Ydi CQHGM GdTQcGJ (BIBS(3, GdVQjHI Ydi GdONd GdELeGdj(BIRG (3, GdVQjHI GdLRGajI GdhMjOI(BIFU(3, GdQSe Ydi GdbjeI GdeVGaI (BTVA(3, GdQSe Ydi GdfTGW Gdegfj(BTAP (3hJMOjO CSGS aQVjI GdVQjHI , GdJNajVGJ hGdEYaGAGJ, VQGFH hQShe CNQi eKd GdQSe GdYbGQj (BTF(3, Mbhb GdJSLjd(BDE (3, Mbhb GdWGHY (BDT (3, GdVQjHI Ydi GdCedGc(BIP (3, hVQGFH ZjQ eHGTQI(B.s
(3eQGLY U(B.169s
Keywords: (3GdVQGFHs; (3LHGjI GdeDSSIs